Respuesta :
x=(x+1)(x+y)
Step 1: Flip the equation.x2+xy+x+y=x
Step 2: Add -x to both sides.x2+xy+x+y+−x=x+−xx2+xy+y=0
Step 3: Add -x^2 to both sides.x2+xy+y+−x2=0+−x2xy+y=−x
2Step 4: Factor out variable y.y(x+1)=−x2
Step 5: Divide both sides by x+1.y(x+1)x+1=−x2x+1y=−x2x+1
So the answer is: y= -x^2/ x+1
Step 1: Flip the equation.x2+xy+x+y=x
Step 2: Add -x to both sides.x2+xy+x+y+−x=x+−xx2+xy+y=0
Step 3: Add -x^2 to both sides.x2+xy+y+−x2=0+−x2xy+y=−x
2Step 4: Factor out variable y.y(x+1)=−x2
Step 5: Divide both sides by x+1.y(x+1)x+1=−x2x+1y=−x2x+1
So the answer is: y= -x^2/ x+1
☆We need to solve for y:
☆Here is the question you asked:
x=(x+1)(x+y)
☆Add -x to both sides:
x^2+xy+x+y+−x=x+−x
x^2+xy+y=0
☆Add -x^2 to both sides:
x2+xy+y+−x^2=0+−x^2
xy+y=−x^2
☆Factor out variable y:
y(x+1)/x+1=−x2/x+1
☆Your answer is:
y=−x2/x+1
☆I hope this helps!☆
☆Here is the question you asked:
x=(x+1)(x+y)
☆Add -x to both sides:
x^2+xy+x+y+−x=x+−x
x^2+xy+y=0
☆Add -x^2 to both sides:
x2+xy+y+−x^2=0+−x^2
xy+y=−x^2
☆Factor out variable y:
y(x+1)/x+1=−x2/x+1
☆Your answer is:
y=−x2/x+1
☆I hope this helps!☆